Culling of Urban Norway Rats and Carriage of Bartonella spp. Bacteria, Vancouver, British Columbia, Canada - Kaylee A. Byers; Michael J. Lee; Janet E. Hill; Champika Fernando; Laura Speerin; Christina M. Donovan; David M. Patrick; Chelsea G. Himsworth (Emerging Infectious Diseases, 2022)
We investigated the effects of culling on Bartonella spp. bacteria carriage among urban rats in Canada. We found that the odds of Bartonella spp. carriage increased across city blocks except those in which culling occurred. Removing rats may have prevented an increase in Bartonella spp. prevalence, potentially lowering human health risks.